Sociodemographic Characteristics of Juvenile Delinquents in Adana - Fırat, Sunay; İltaş, Yiğit and Gülmen, Mete Korkut (The Bulletin of Legal Medicine, 2016)
Introduction: There are a variety of risk factors which push children to delinquency. Personal and familial difficulties experienced by the children during the adolescence period, negative effects of intensive and uncontrolled migrations on the children and their families, inappropriate peer relationships of children, low socio-economic status of children and their families and their illiteracy, usage of alcohol and/or drugs by the children are some of these factors. In this study, socio-demographic date of children pushed to delinquency, their family traits, types of their crimes, age of committing crimes and the fact that whether they commit crime alone or with the participation of more than one person, their migration status for their vicinities have been put forward statistically. Materials and Methods :Data belonging to children between 0 and 18 ages who have come or have been made to come to 1, 2, 3 Numbered Juvenile Courts of Adana Court House as of January 2004 with the claim of their committing crime and data (information in court decisions and Social Study Report (SSR) that are demanded by court decision) about children who have been sent/have applied to Provincial Directorate for National Education because of injunctions by court decision have been evaluated retrospectively. Results: Out of 258 children in our study, 225 was male (87.2%) and 33 (12.8%) was female; average age of these children pushed to delinquency was 13 years 4 months ±2.20 (min: 5 years 8 months, max:17 years 9 months). 45% of children have committed crime against property; 23.3% against people; 3% committed terror crime. 27.5% of children have been put under protection due to their working in the streets. It is found that there is a meaningful relationship between crime types of children pushed to crime and migration status of the families of the children (p=0.028). Discussion: Socio-demographic features which may affect delinquency directly or indirectly according to us have been aimed to be shown in our study. Protective and supportive precautions can be taken for children pushed to delinquency within the scope of child protection law in our country. Reasons of delinquency, prevention ways and studies to reintroduce these children to the society are primary issues for all societies. As a consequence, stating the risk factors belonging to family, school, society and the child for the prevention of delinquency and finding solutions for these facts are needed. Keywords: juvenile delinquency; risk factors; epidemiology; socio-demographic characteristics